1986
DOI: 10.1161/01.cir.73.6.1213
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of the Björk-Shiley, Hancock, and Carpentier-Edwards heart valve prostheses.

Abstract: From 1975to 1979 patients undergoing valve replacement were entered into a randomized trial and received either a Bjdrk-Shiley (273 patients) or a porcine heterograft prosthesis (initially a Hancock valve [107 patients] and later a Carpentier-Edwards prosthesis [ 160 patients]). Two hundred and sixty-two patients required mitral valve replacement, 210 required aortic valve replacement, 60 required mitral and aortic valve replacement, and eight also required associated tricuspid valve replacement (six mitral va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(15 citation statements)
references
References 24 publications
(9 reference statements)
1
12
2
Order By: Relevance
“…The type of patients examined in our study is comparable to these by guest on May 9, 2018 http://stroke.ahajournals.org/ Downloaded from reports, with some limitations. First, the percentage of patients with CE valves who were on anticoagulation therapy was 49% for mitral and 6% for aortic valves in one study, 22 not stated in the other, 21 and 84% in the present study. Second, patients in the previous studies had convex-concave BS and standard CE valves, whereas the majority of patients with BS valves in our study had the monostrut type, and 34% of patients with a CE valve had the supra-annular type.…”
Section: Discussioncontrasting
confidence: 49%
“…The type of patients examined in our study is comparable to these by guest on May 9, 2018 http://stroke.ahajournals.org/ Downloaded from reports, with some limitations. First, the percentage of patients with CE valves who were on anticoagulation therapy was 49% for mitral and 6% for aortic valves in one study, 22 not stated in the other, 21 and 84% in the present study. Second, patients in the previous studies had convex-concave BS and standard CE valves, whereas the majority of patients with BS valves in our study had the monostrut type, and 34% of patients with a CE valve had the supra-annular type.…”
Section: Discussioncontrasting
confidence: 49%
“…They concluded that early anticoagulation to maintain a prothrombin time between 1.5 and 2.0 (INR 3.0-4.5) should be administered for at least 3 months. This high level of anticoagulation might explain the higher rate of bleeding complications observed in these patients compared with previous reports [11,47,48]. They did not, however, distinguish between prostheses in the mitral and aortic positions.…”
Section: Literature Reviewcontrasting
confidence: 58%
“…The majority of patients (30 of 42) were taking warfarin (14) or aspirin (16) at the time of the study. In group A, 12 of 15 (6 warfarin, 6 aspirin) were being treated; 11 of 13 (6 warfarin, 5 aspirin) in group B and 7 of 14 (2 warfarin, 5 aspirin) in group C were being treated.…”
Section: Resultsmentioning
confidence: 99%